Laboratory testing of extravascular body fluids : national recommendations on behalf of the Croatian Society of Medical Biochemistry and Laboratory Medicine : part I : serous fluids - Milevoj Kopčinović, Lara (Array, 2020)
Extravascular body fluids (EBF) analysis can provide useful information in the differential diagnosis of conditions that caused their accumulation. Their unique nature and particular requirements accompanying EBF analysis need to be recognized in order to minimize possible negative implications on patient safety. This recommendation was prepared by the members of the Working group for extravascular body fluid samples (WG EBFS). It is designed to address the total testing process and clinical significance of tests used in EBF analysis. The recommendation begins with a chapter addressing validation of methods used in EBF analysis, and continues with specific recommendations for serous fluids analysis. It is organized in sections referring to the preanalytical, analytical and postanalytical phase with specific recommendations presented in boxes. Its main goal is to assist in the attainment of national harmonization of serous fluid analysis and ultimately improve patient safety and healthcare outcomes. This recommendation is intended to all laboratory professionals performing EBF analysis and healthcare professionals involved in EBF collection and processing. Cytological and microbiological evaluations of EBF are beyond the scope of this document.